Mechanical Design and Dynamic Analysis of Pipe Crawling Robot for 6” to 10” diameter Internal Gas Pipeline Inspection - Mohd Amirul Bin Che Hussain, Mohd Amirul (Universiti Teknologi Petronas, 2012)
With the world moving forward, robot has been considered as an attractive and innovative alternative to help human in their work. For oil and gas industry, pipelines have been an important asset that needs to be maintained always. For many centuries, it has been integrals part of our constructions. However, with the cost of maintenance continue to increase, a new approach needed to accomplishing them. Many different types of pipelines robot have been proposed in the past. Unfortunately, many of the robot work under very restricted area or environments such as customized pipes sometimes have no vertical movement or can traverse through only a simple pipeline structure. This project is targeted to build and design a functional robot where the application can be tailored to internal pipelines inspection and maintenance. With overcome the existing problem from the past pipeline inspection robot, a new and improved design will help in constructing the robot. The scope of this project is focused on mechanical and structural design of the pipe crawling robot. The methodology of this project will be involving research and identification, conceptual and system design including analysis, construction of the prototype, simulation testing and analysis and completing the final report. In the end of this project will be able to develop a simulation model of pipe crawling robot for internal pipeline inspection. The related mechanical model and analyzing of the mechanical design and active adaption to pipe diameter, tractive force adjusting, control system structure are discussed. As a pipe crawling robot for visual inspection, this project can become the fundamental for other inspection robot